Identifying critical challenges in the adoption of cloud‐based services. (18th January 2017) - Rahi, Shiromani Balmukund; Bisui, Sandip; Misra, Subhas Chandra
Summary: Cloud computing provides a way to integrate and share information on a real‐time basis across an organization. The current organizations are adopting the cloud services to gain competitive advantage in real‐time data sharing. To meet the current demand in semiconductor industries, they must develop better techniques to produce electronic products at low cost and in a large scale. Adoption of cloud‐based services may resolve the fastest growing demand of technical advancement of semiconductor industries. The research presented in this paper is based on an analysis of the data obtained from the semiconductor sector. This study identifies the critical challenges associated with the cloud service adoption in semiconductor industries. Twelve critical challenges have been identified that need to be overcome for adopting the cloud services for any semiconductor industry. These are network/Internet availability, data security, integration of various services, monitoring of data and services, maintenance of computing performance, liability, power outage, service interruption, organizational change, business complexity, legal issues, and lack of awareness. Abstract : Twelve critical challenges have been identified that need to be overcome for adopting the cloud services for any semiconductor industry. These are network/Internet availability, data security, integration of various services, monitoring of data and services, maintenance of computing performance, liability, power outage, service interruption, organizational change, business complexity, legal issues, and lack of awareness.